Paediatric trauma care - Sebastian van As A (Wolters Kluwer Medknow Publications, 2010)
Background: Childhood trauma has become a major cause of mortality and morbidity, disability and socio-economic burden and it is expected by the World Health Organization (WHO) that by 2020 it will be the number 1 disease globally. The WHO and UNICEF have published their third World Report on Child Injury Prevention in December 2008. Materials and Methods: A systematic review was performed on the history and magnitude of paediatric trauma worldwide. Additionally exciting developments and new trends were assessed and summarized. Results: Paediatric trauma is a growing field of clinical expertise. New developments include total body digital imaging of children presenting with polytrauma; targeted management of head injuries; conservative management of abdominal injuries in children and diagnostic laparoscopy, including the laparoscopic management of complications following the conservative management of solid organ injuries. Conclusion: Paediatric trauma has long been neglected by the medical profession. In order to deal with it appropriately, it makes sense to adopt the public health approach, requiring that we view child injuries similarly to any other disease or health problem. The greatest gain in our clinical practice with dealing with child injuries will result from a strong focus on primary (preventing the injury), secondary (dealing with the injury in the most efficient manner) as well as tertiary prevention (making sure that children treated for trauma will be appropriately reintegrated within our society). By actively promoting child safety we will not only achieve a most welcome reduction in medical cost and disability, but also the ever-so-much desired decline of avoidable childhood misery and suffering.